Incidence and cause of acute confusion in elderly patients (Faculty of Medicine Universitas Indonesia, 2002)
Acute confusion is a clinical syndrome in the elderly whose diagnosis is made by acute onset of disturbance of consciousness, impairment of cognition and fluctuating perception and has an underlying medical cause associated with usually serious medical illness. Acute confusion has a high morbidity and mortality, and patient need to stay longer in the hospital, have a higher risk for institutionalization and immobilization. The aim of this study is to recognize the incidence and most of medical illness, which cause acute confusion in elderly patients, a retrospective study based on medical record of elderly patients who were hospitalized in Dr Kariadi hospital since 1998 to 1999. 5407 elderly patients were hospitalized, but only 5191 were analyzed and included in this study. 35% (992 men and 846 women) elderly patients had acute confusion on first arrival and 7% ( 197 men and 176 women) acute confusion appears in the ward. Total acute confusion was 40.89%. The mortality rate was 29% (263 women and 381 men). Three most frequent cause of death were sepsis (10.04%); hemorrhagic stroke (5.11%); multifactor (4.16%). Top ten diseases, which cause acute confusion, were hepatic encephalopathy, hemorrhagic stroke, sepsis, moderate dehydration due to gastoenteritis, hyponatremia, acute myocardial infarction, pneumonia, urinary tract infection, congestive heart failure, and arrhythmia cordis. (Med J lndones 2002; 11: 30-35)Keywords: acute confusional state, geriatric patients, hospital study